Acute nicotine induces anxiety and disrupts temporal pattern organization of rat exploratory behavior in hole-board: a potential role for the lateral habenula - Casarrubea, Maurizio; Davies, Caitlin; Faulisi, Fabiana; Pierucci, Massimo; Colangeli, Roberto; Partridge, Lucy; Chambers, Stephanie; Cassar, Daniel; Valentino, Mario; Muscat, Richard; Benigno, Arcangelo; Crescimanno, Giuseppe; et al. (Frontiers in Cellular Neuroscience, 2015)
Abstract Nicotine is one of the most addictive drugs of abuse. Tobacco smoking is a major cause of many health problems, and is the first preventable cause of death worldwide. Several findings show that nicotine exerts significant aversive as well as the well-known rewarding motivational effects. Less certain is the anatomical substrate that mediates or enables nicotine aversion. Here, we show that acute nicotine induces anxiogenic effects in rats at the doses investigated (0.1, 0.5, and 1.0 mg/kg, i.p.), as measured by the hole-board apparatus and manifested in behaviors such as decreased rearing and head-dipping and increased grooming. No changes in locomotor behavior were observed at any of the nicotine doses given. T-pattern analysis of the behavioral outcomes revealed a drastic reduction and disruption of complex behavioral patterns induced by all three nicotine doses, with the maximum effect for 1 mg/kg. Lesion of the lateral habenula (LHb) induced hyperlocomotion and, strikingly, reversed the nicotine-induced anxiety obtained at 1 mg/kg to an anxiolytic-like effect, as shown by T-pattern analysis. We suggest that the LHb is critically involved in emotional behavior states and in nicotine-induced anxiety, most likely through modulation of monoaminergic nuclei.